Spin-flip hot spots in ultrathin films of monovalent metals: Enhancement and anisotropy of the Elliott-Yafet parameter - Long, Nguyen H.; Mavropoulos, Phivos; Heers, Swantje; Zimmermann, Bernd; Mokrousov, Yuriy; Blügel, Stefan (PHYSICAL REVIEW B, 2013)
In contrast to the long-known fact that spin-flip hot spots, i.e., special k points on the Fermi surface showing a high spin-mixing parameter, do not occur in the bulk of monovalent (noble and alkali) metals, we found them on the surface Brillouin-zone boundary of ultrathin films of these metals. Density-functional calculations within the Korringa-Kohn-Rostoker Green function method for ultrathin (001) oriented Cu, Ag, and Au films of 10-layer thickness show that the region around the hot spots can have a substantial contribution, e. g., 52% in Au(001), to the integrated spin-mixing parameter, that could lead to a significant enhancement of the spin-relaxation rate or spin-Hall angle in thin films. Owing to the appearance of spin-flip hot spots, a large anisotropy of the Elliott-Yafet parameter {[}50% for Au(001)] is also found in these systems. The findings are important for spintronics applications in which noble metals are frequently used and in which the dimensionality of the sample is reduced.